2008
DOI: 10.1373/clinchem.2007.093658
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Melting Analysis of the spa Repeat Region of Staphylococcus aureus

Abstract: BACKGROUND:The staphylococcal protein A (spa) locus of Staphylococcus aureus contains a complex repeat structure and is commonly used for single-locus sequencebased genotyping. The real-time PCR platform supports genotyping methods that are single step and closed tube and potentially can be carried out simultaneously with diagnosis. We describe here a method for genotyping S. aureus using high-resolution melting (HRM) analysis of the spa polymorphic region X.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 18 publications
5
50
1
6
Order By: Relevance
“…Such hypervariable genes are potentially amenable to HRM analysis. This has been demonstrated with the Campylobacter jejuni CRISPR and fla loci (12) and the S. aureus spa locus (19,22). Those studies demonstrated that HRM can resolve significant numbers of alleles of individual loci.…”
Section: Figmentioning
confidence: 87%
“…Such hypervariable genes are potentially amenable to HRM analysis. This has been demonstrated with the Campylobacter jejuni CRISPR and fla loci (12) and the S. aureus spa locus (19,22). Those studies demonstrated that HRM can resolve significant numbers of alleles of individual loci.…”
Section: Figmentioning
confidence: 87%
“…It is also no more complex or labour intensive to perform than a simple PCR; it does not require purification and/or cloning of the amplicons, nor enzyme digestion or gel electrophoresis for single-strand conformation polymorphism, nor any kind of hybridization with probes on a solid support. In optimal conditions, it has been demonstrated that HRM analysis has almost 100% accuracy (Reed and Wittwer, 2004) and it has previously been adapted for several microbiological applications such as rapid identification of Staphylococcus aureus genotypes and influenza subtypes (Lin et al, 2008;Stephens et al, 2008). In addition, HRM has been applied in scanning human genome DNA for several disease causing polymorphisms (reviewed in Erali et al, 2008), while at the Rudjer Boskovic Institute it has previously been Sabol, I., Čretnik, M., Hadžisejdić, I., Si-Mohamed, A., Matovina, M., Grahovac, B., Levanat, S., Grce, M., 2009.…”
Section: Discussionmentioning
confidence: 99%
“…HRM analysis of 44 diverse MRSA isolates carried out by Stephens and coworkers generated 20 profiles from 22 spa sequence types. The two unresolved HRM spa types differed by only 1 bp (Stephens et al, 2008). Surprisingly good results of genotyping of C. jejuni were obtained by HRM scanning of polymorphism of several targets: a regularly interspaced short-palindromic-repeat (CRISPR) locus (Price et al, 2007) 75 2010).…”
Section: High Resolution Melting Analysis -Hrmmentioning
confidence: 99%